2019
DOI: 10.3390/nano9030331
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ethylene with Irn (n = 1–10): From Bare Clusters to γ-Al2O3-Supported Nanoparticles

Abstract: Comprehending the bond nature of ethylene-metal clusters at the atomic level is important for the design of nanocatalysts and their applications in the fields of fine chemistry and petroleum refining. The growth of Irn (n = 1–10) on γ–Al2O3(110) and ethylene adsorption on bare and γ–Al2O3(110)-supported Irn (n = 1–10) clusters were investigated using the density functional theory (DFT) approach. The mode stability of ethylene adsorption on the bare Irn clusters followed the order π > di-σ > B-T, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The interfacial structure is widely confirmed to influence the properties of the composites [75], such as the resistance towards carbon deposition during Ni-based catalysts catalyzing DRM [76]. Recently, studies have shown that adjusting the interface and strengthening the interaction between Ni and the support play a vital role in the synthesis of efficient and stable Ni-based DRM catalysts.…”
Section: Interface Structure Controlmentioning
confidence: 99%
“…The interfacial structure is widely confirmed to influence the properties of the composites [75], such as the resistance towards carbon deposition during Ni-based catalysts catalyzing DRM [76]. Recently, studies have shown that adjusting the interface and strengthening the interaction between Ni and the support play a vital role in the synthesis of efficient and stable Ni-based DRM catalysts.…”
Section: Interface Structure Controlmentioning
confidence: 99%
“…Rapid advances in nanoscience and nanotechnology enable the creation of nanomaterials with unique properties and superior features, which have been widely applied in many research areas, including biosensing, biomedicine, catalysis, and energy storage. A typical example among them is the nanozyme, which possesses intrinsic enzyme-mimicking characteristics as a new generation of artificial enzymes. Significant research efforts have been made to explore nanozymes because of the unparalleled features of easy preparation, low cost, and high stability.…”
Section: Introductionmentioning
confidence: 99%